Prevalence and antimicrobial susceptibility patterns of uropathogenic E. coli among people in Zakho, Iraq - Polse, Reem Fouad; Yousif, Samira Younis; Assafi, Mahde Saleh (International Journal of Research in Medical Sciences, 2016)
Background: Antimicrobial resistance in uropathogenic E. coli is of major concern worldwide due to its increasing resistance to several commonly prescribed antibiotics. The aims of this study were to determine the prevalence and to evaluate the presence and antibiogram pattern of uropathogenic E. coli among people in Zakho city, Iraq. Methods: 1120 urine samples were collected from people. Samples were screened for E. coli isolates and their susceptibility to different antibiotics was analyzed. Results: Diagnoses tests showed that only 106 (9.4%) isolates were E. coli. Females (90, 85%) were more susceptible to urinary tract infections (UTIs) than males (16, 15%) (p <0.05). The age 11-21 years old (23, 21.7%) was the most affected group (p <0.05). All isolates were resistant to penicillin, ampicillin and aztreonam. While, all these isolates were sensitive to imipenem and meropenem. Conclusions: The incidence of uropathogenic E. coli among people is comparable with reports from elsewhere. E. coli isolates are highly susceptible towards imipenem, and meropenem antibiotics, and highly resistant towards β-lactam and cephalosporins antibiotics. Education programs and improving the hygienic measures are necessary to prevent contaminations with E. coli and minimize the use of β-lactam and cephalosporin antibiotics.